Effect of Combined Probiotics (Saccharomyces cerevisae + Candida utilis) and Herbs on Carcass Characteristics of Swamp Buffalo - Mahyuddin, P; Widiawati, Y (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2010)
A feedlot trial was conducted to study the effect of probiotics + herbs on carcass characteristics. Thirty male swamp buffaloes aged 2â2.5 years with the average body weight of 297 kg were used in this trial. They were fattened for 75 days to reach a slaughter weight of around 350â400 kg. They were divided into two groups of 15 animals in each group, and were placed in a shaded paddock. The groups were the control and the treated animals. The treated animals were given a supplementation containing combined yeasts (Saccharomyces cerevisae and Candida utilis), and herbs. All animals were fed basal diet of ammoniated rice straw and commercial concentrate with a ratio of 10: 90. There was no effect of probiotics+herbs on live weight gain, percentage of carcass, dressing, meat and by products, back fat thickness and eye muscle area. Addition of probiotics+herbs increased proportion of bone, reduced meat : bone ratio, body fat and proportion of offal. Although body fat content was reduced by the treatment, the compositions of fat were similar between the control and treated animals. (Animal Production 12(2): 69-73 (2010)Key Words: buffalo, feedlot, yeast, carcass